2002
DOI: 10.1046/j.1365-2869.2002.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

CSF hypocretin‐1 (orexin‐A) concentrations in narcolepsy with and without cataplexy and idiopathic hypersomnia

Abstract: We measured cerebrospinal fluid (CSF) hypocretin‐1 levels in 11 patients with narcolepsy–cataplexy, five with narcolepsy without cataplexy and 12 with idiopathic hypersomnia (IHS). All patients were Japanese. As reported in Caucasian patients, undetectable or very low hypocretin‐1 levels were observed in most (9 out of 11) Japanese narcolepsy–cataplexy patients. Our hypocretin‐deficient narcoleptics included three prepubertal cases within few months after the disease onset. All nine hypocretin‐deficient patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
3
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(104 citation statements)
references
References 5 publications
5
92
3
4
Order By: Relevance
“…12 It has been reported that SNP rs1154155 located in TCRA locus was associated with hypocretin deficient narcolepsy with cataplexy. 4 Meanwhile, the CSF hypocretin-1 levels of most of the narcoleptics without cataplexy are within the normal range except for some cases, 6,13 indicating that many of the EHS patients might not be hypocretin deficient and SNP rs1154155 might also be associated with hypocretin non-deficient hypersomnias. However, the CSF hypocretin-1 measurements were not performed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…12 It has been reported that SNP rs1154155 located in TCRA locus was associated with hypocretin deficient narcolepsy with cataplexy. 4 Meanwhile, the CSF hypocretin-1 levels of most of the narcoleptics without cataplexy are within the normal range except for some cases, 6,13 indicating that many of the EHS patients might not be hypocretin deficient and SNP rs1154155 might also be associated with hypocretin non-deficient hypersomnias. However, the CSF hypocretin-1 measurements were not performed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, nearly all individuals with N-C have normal CSF concentrations of hypocretin. 1,11,12 Considering the role of hypocretin in reward-seeking behavior and addiction, we hypothesized that individuals with N+C (low or absent CSF hypocretin) would show less risk-taking behavior than individuals with N-C (normal hypocretin levels).…”
Section: Part I: Questionnairesmentioning
confidence: 99%
“…In contrast, nearly all individuals with N-C have normal CSF concentrations of hypocretin. 1,11,12 We excluded subjects with a prior history of addiction, substance abuse, or psychiatric illness. This may seem counterintuitive, as these exclusion criteria are directly related to our main hypothesis.…”
Section: Limitationsmentioning
confidence: 99%
“…These neurons are located in the ventral lateral hypothalamic nucleus in dogs and have extensive connections throughout the central nervous system (CNS) that promote wakefulness and muscle tone in response to the release of hypocretin 6. Humans with primary narcolepsy who suffer from cataplexy as part of their disease are classified as type 1, and the majority have low or undetectable levels of hypocretin in the CSF 7, 8, 9. In type 2 primary narcolepsy, cataplexy is not a component, and CSF hypocretin levels are normal.…”
mentioning
confidence: 99%